أثر الفرص التسويقية في تطوير المنتج: دراسة تحليلية لآراء عينة من معامل الالبان الخاصة - نضال بدر شيت (PROSPECTIVE RESEARCHES, 2023)
The research aims at determining the correlation and effect between the opportunities Altsoeqh and product development which, has been applied at Al-Bakara al Jamella Dairy factory and Al-Jazeera Dairy Factory in the city of Mosul Through a form questionnaire distributed to thirty managers and heads of departments of booth organizations. (SPSS) program is applied for the purpose of analyzing the data collected from the specimen. Generally, the research tries to find answers the following questions: 1. Is there a clear vision of the two organizations which have undergone research for marketing opportunities and product development? 2. Is there a relationship between the significant marketing opportunities and product development? 3. Is there a significant effect of the marketing opportunities in product development? 4. Is there a contrast in the responds of the specimen about the marketing opportunities and the development of traffickers? The research found a set of conclusions and the most important is the significant correlation between the significant of marketing opportunities and product development. In addition, it provides a set of proposals. The most important proposal is the necessity of marketing internal and external environmental analyses in order to make use of marketing opportunities and product development in the laboratory.